The Semantics of Wild Nature in N. M. Karamzin’s Works: was Karamzin the Russian Henry Thoreau? - Снежко, Юлия (Literatūra, 2017)
This article deals with the semantics of wild nature, found in Karamzin’s works. The author tries to answer the question of what Karamzin himself considered European or Russian wild nature to be. The concretization of the meaning of wild nature in Karamzin’s works seems relevant if we have in mind the big number of literary and cultural researches (within the frame of ecocriticizm and not only) that analyze wild nature. Though a considerable amount of scientific literature has been devoted to the theme of nature in Karamzin’s works, the notion of wild nature hasn’t been systematically investigated. In this article, attention is paid to the contexts in which nature is referred to as “wild.”Here, it is shown that Karamzin’s relation to wild nature was ambivalent. The semantics of European and Russian wild nature are different and have both positive and negative aspects. This difference is explained by the specifics of the aesthetical optics of the narrator (the aesthetics of the picturesque or the sublime) and by his narrative position (a personalized relationship toward nature or a governmental point of view). Wild nature that is aesthetically attractive to Karamzin is the one that minimally experienced the influence of man and is part of picturesque aesthetics, or the nature that it is the quintessence of the sublime –the mountains. However, wild nature that didn’t experience the influence of man and that is not part of the picturesque aesthetics, as it is with the bigger part of Russian nature (steppes, forests, marshes, empty spaces) does not have such a pleasing effect; on the contrary, it frightens the narrator, and from the governmental point of view – which Karamzin shares – it should be controlled and subdued. In this article, it is concluded that Karamzin was not the Russian Henry Thoreau, and his relationship toward wild nature, both positive and negative, was mostly based on the ideology of the Enlightenment.LAUKINĖS GAMTOS SEMANTIKA N. M. KARAMZINO KŪRYBOJE: AR KARAMZINAS BUVO RUSIŠKUOJU HENRIU TOROŠiame straipsnyje analizuojama laukinės gamtos semantika N. Karamzino kūryboje. Darbe tikslinama, ką Karamzinas laikė laukine europietiška ir rusiška gamta. Laukinės gamtos sampratos tikslinimas Karamzino darbuose yra aktualus, turint omenyje nemažą skaičių literatūrinių bei kultūrinių tyrimų (ekokritikos ir ne tik jos rėmuose), kuriuose tiriama laukinė gamta. Nors gamtos tematika Karamzino kūryboje nėra nauja mokslininkų akiratyje, tačiau laukinės gamtos samprata sistemingo tyrimo nesusilaukė. Straipsnyje atkreipiamas dėmesys į tai, kokiuose kontekstuose gamta įvardijama kaip „laukinė“.Šiame straipsnyje parodoma, kad Karamzino požiūris į laukinę gamtą buvo ambivalentiškas. Europietiškos ir rusiškos laukinės gamtos semantika skiriasi ir turi tiek neigiamą, tiek teigiamą aspektą. Šis skirtumas aiškinamas pasakotojo estetinės optikos ypatumais (vaizdingumo / pakylėtumo estetika) bei jo pasakojimo pozicija (suasmenintu santykiu ar valstybine perspektyva). Estetiškai Karamziną žavi laukinė gamta, kuri minimaliai patyrė žmogaus įtaką ir atitinka vaizdingumo reikalavimus arba pakylėtumo estetikos kvintesenciją – kalnai. Tačiau laukinė gamta, nepatyrusi žmogaus įtakos arba neatitinkanti vaizdingumo reikalavimų, kaip yra su didžiausia Rusijos gamtos „dalimi“ (stepės, miškai, pelkės, tuščios erdvės), ne tiek žavi, kiek baugina pasakotoją, ir valstybinės perspektyvos požiūriu turi būti kontroliuojama. Straipsnyje daroma išvada, kad Karamzinas nebuvo rusiškuoju Henriu Toro, o jo požiūris į laukinę gamtą, tiek negatyvus, tiek ir pozityvus, daugiausiai išreiškė Apšvietos epochos ideologiją.
Keywords: Karamzin; Thoreau; Wild nature; Landscape; Space; Enlightenment